2020
DOI: 10.2217/fon-2020-0187
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Evidence of NEPA, Netupitant-Palonosetron, in Chemotherapy-Induced Nausea and Vomiting Prevention: Effects on Quality of Life

Abstract: Aim: To determine quality of life, effectiveness and safety of oral netupitant-palonosetron (NEPA)–based antiemetic prophylaxis in the real-world setting. Materials & methods: Prospective, noninterventional study in adults receiving highly or moderately emetogenic chemotherapy and NEPA for three cycles. NEPA was administered per summary of product characteristics. Results: A total of 2429 patients enrolled, 2173 were evaluable. ‘No impact on daily life’ due to vomiting was reported by 85%/82% of patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 45 publications
(77 reference statements)
3
39
0
9
Order By: Relevance
“…Simple administration schedules not only could facilitate adherence by physicians but also could prevent patients from making medication mistakes, a recurring problem during home administration in the delayed phase [32]. In line with this, a recent noninterventional study evaluating patient‐reported outcomes during the use of NEPA in routine clinical practice showed similar antiemetic efficacy as in the controlled pivotal trials, suggesting high treatment compliance by patients under real‐world conditions [46]. On the other hand, a recent phase IV study demonstrated lower antiemetic effectiveness of the aprepitant/fosaprepitant‐palonosetron‐dexamethasone regimen in the real world as compared with the reported efficacy in randomized controlled trials [47, 48].…”
Section: Discussionmentioning
confidence: 93%
“…Simple administration schedules not only could facilitate adherence by physicians but also could prevent patients from making medication mistakes, a recurring problem during home administration in the delayed phase [32]. In line with this, a recent noninterventional study evaluating patient‐reported outcomes during the use of NEPA in routine clinical practice showed similar antiemetic efficacy as in the controlled pivotal trials, suggesting high treatment compliance by patients under real‐world conditions [46]. On the other hand, a recent phase IV study demonstrated lower antiemetic effectiveness of the aprepitant/fosaprepitant‐palonosetron‐dexamethasone regimen in the real world as compared with the reported efficacy in randomized controlled trials [47, 48].…”
Section: Discussionmentioning
confidence: 93%
“…Another example of reduced effectiveness in a real‐world setting was shown in a recent prospective, observational trial exploring the effectiveness of aprepitant/fosaprepitant in a heterogenous population receiving predominantly cisplatin‐based HEC or AC; an overall complete response rate of just 34% was seen in the AC subset [33]. A prior NEPA real‐life noninterventional study was conducted in a large heterogenous population of 2,173 patients with various tumor types receiving a variety of HEC and MEC [34]. Reassuringly, the response rates seen in that study were consistent with those shown in the pivotal NEPA studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the effectiveness of oral netupitant/palonosetron in preventing CINV in the real-world setting is available from a prospective, non-interventional study conducted in Germany in 2429 adults receiving HEC or MEC for three cycles [ 27 ]. Netupitant/palonosetron was administered according to the EU label (Sect.…”
Section: Therapeutic Efficacy Of Nepamentioning
confidence: 99%
“…In the HEC and MEC groups, respectively, 84–88% and 82–87% of patients reported no impact on daily life (NIDL) due to vomiting across cycles 1–3, 54–58% and 59–66% reported NIDL due to nausea, and 64–66% and 67–74% reported NIDL for the combined domain of nausea and vomiting [ 27 ]. Overall, high CR rates were also observed across cycles 1–3 (89.2–90.9%, 86.9–87.1% and 82.5–83.6% in the acute, delayed and overall phases, respectively).…”
Section: Therapeutic Efficacy Of Nepamentioning
confidence: 99%